On Some Methodological Approaches to Investigation of Political Parties - Kuznecova, Tatyana (History / Istorija, 2019)
Some different approaches to the research of political parties (sociological, institutionalist, structural-functional) used by sociologists and historians are analysed in the paper, and the systematic individualised study of political parties is offered as well.